Dampak COVID-19 Terhadap Pendapatan Pedagang Sayur di Pasar Tradisional - Faisal Y. Habsyi; Samil Wayaro (Peneliti.net, 2022)
The Corona Virus Disease that occurred in 2019 had a broad impact on all aspects of people's lives in the world. The economic condition of the community, especially the middle class and lower class people, has also been affected by the COVID-19 pandemic, including traders in traditional markets. The income of traditional market traders has decreased very significantly, including the income of vegetable traders at the Gamalama traditional market in Ternate. In researching the impact of COVID-19 on the income of vegetable traders in traditional markets (study on the Gamalama Ternate market) using a qualitative descriptive research method with the number of research subjects as many as 20 vegetable traders in the Ternate Gamalama traditional market. The results obtained from the study found that there was a decrease in the income of vegetable traders by 38.86% compared to the income before COVID-19 or the average monthly income of Rp. 2,905,000 before the COVID-19 pandemic dropped to Rp. 1,128,750 during the COVID-19 pandemic.